Archaeometrical Characterization of Romanian Late Bronze Age Ceramic Fragments - Fierascu, Irina; Baroi, Anda Maria; Brazdis, Roxana Ioana; Fistos, Toma; Nicolae, Cristian Andi; Raditoiu, Valentin; Inel, Ioan Constantin; Sava, Victor; Fierascu, Radu Claudiu (Frontiers in Materials, 2021)
Knowledge of the past can provide information to protect the future and the potential of the technological development in the analytical area can be successfully applied for the study and conservation of cultural objects. In this context, in the present paper we propose an analytical methodology to characterize seven samples of ancient ceramic objects (dating to the Late Bronze Age). The samples were analyzed using optical microscopy, and all the samples presented a strong inhomogeneity on the surface, as suggested by the different colors of the ceramics. X-ray fluorescence (XRF) results reveal a relatively heterogenous composition of the samples, as well as strong differences between the different surfaces of each sample. By comparative analysis of the diffractograms recorded for both sides of the same samples were observed some differences, especially in terms of relative concentration of the component minerals, and, in lesser content, in terms of new phases present in the samples. Corroborated results obtained by XRF and X-ray diffraction (XRD) offered information regarding mineralogical composition of the samples: for some of them illite/muscovite and plagioclase phases are present in higher quantities or a lower quartz content. The presence of these components was confirmed by Fourier-transform infrared spectroscopy (FTIR) analysis. The thermal analysis completes the analytical investigation of the ceramic samples. The thermal behavior of the sample conducted to some explanation regarding raw materials (that the major clay mineral in the samples is represented by illite) or to environmental factors during their burial in the soil.